Life Cycle Homes for Adaptability, Circularity, and Sustainability - Avi Friedman (Architecture, 2025)
In the realm of housing, the concept of adaptability has emerged as a pivotal solution to address the evolving space needs of households. The hypothesis and contribution that this paper puts forward is that dwellings can be designed to accommodate society’s demographic transformation and facilitate the evolving interior space needs of their occupants. It investigates the concept of Life Cycle Homes manifested through designs of flexible living spaces that can be easily modified to align with the changing dynamics of family structures over time to achieve user satisfaction, circularity, and sustainability. The investigation begins with an exploration of contemporary demographic shifts and variations in family sizes. The discussion underscores how different types of families interact with their homes, highlighting the necessity for adaptable housing solutions. The paper then continues with the study of past theories and application in adaptable housing, most notably through the work of Habraken and Japanese housing innovation. A detailed examination of various flexible housing strategies is presented, focusing on innovative approaches like demountable partitions. These strategies are instrumental in creating versatile living spaces that can seamlessly adapt to households’ diverse and dynamic requirements. Following a research and development process, and as part of the methodology, the paper introduces the Life Cycle Home project that was conceived by the author to illustrate a practical implementation of adaptable housing strategies. The three-floors home exemplifies how flexibility and versatility can meet the changing needs of homeowners, offering a blueprint for future residential design.